The Representation of the Filipino community by a Filipino-American comedienne also known as Happyslip - Ycong, Nina Bernice 1990-; Tolentino-Canlas, Daphne Tatiana (Quezon City College of Mass Communication, University of the Philippines Diliman, 2011)
"This research aims to present a discourse on the identity that emigrants describe of their homeland through the videos of a Filipino-American comedienne, in the context of her portrayal of her Filipino family. Youtube, being one of the most or probably even the most popular video sharing website in the world, has made a certain Christine Gambito famous because of her channel called HappySlip. She coined HappySlip, which she also regards as her alias, from her Filipino mother's mispronounciation of "half slip". HappySlip is a one-woman production that humorously presents a series of videos mostly about ethnic habits of a Filipino family as seen through the eyes and mind of an American. Gambito is the one who plays the many characters of different members of her family - her mother, her father, her aunt, her cousin and her grandmother whom she calls lola. This research mainly revolves around the discourse of how Filipino-American describe the Filipino community and will use the videos of HappySlip as a case study. It seeks to identify the relationship between her orientation as a Filipino who was born and raised in America and the way by which she represents her Filipino family. In exploring this relationship, a descriptive textual analysis will be conducted to identify the indicators of ethnicity within the stories in her videos that may speak of being Filipino but avoid the instance of being essentialist."
Undergraduate thesis